Familial nasal acilia syndrome. Issue 1 (July 1996) - Soferman, R; Ne'man, Z; Livne, M; Avital, A; Spirer, Z
Abstract : Mucociliary dysfunction can be caused by the absence of cilia or by abnormalities in their ultrastructure. A family in which some members were suffering from respiratory morbidity due to lack of cilia is described.